2016
DOI: 10.1186/s12934-016-0459-x
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of S-adenosylmethionine biosynthesis and regeneration improves methylation in the E. coli de novo vanillin biosynthesis pathway

Abstract: BackgroundVanillin is an industrially valuable molecule that can be produced from simple carbon sources in engineered microorganisms such as Saccharomyces cerevisiae and Escherichia coli. In E. coli, de novo production of vanillin was demonstrated previously as a proof of concept. In this study, a series of data-driven experiments were performed in order to better understand limitations associated with biosynthesis of vanillate, which is the immediate precursor to vanillin.ResultsTime-course experiments monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 61 publications
2
92
0
1
Order By: Relevance
“…Finally, we found that coordinated, global perturbation of SAM biosynthesis was obtainable through a single CRISPRi intervention, leading to increased conversion through the anthocyanin O -methylation tailoring reaction. The metJ dysregulation strategy described in this and another recent report [25] should be useful for improving methylation of any natural product, but the general steps taken here should also be applicable for studying unique anthocyanin tailoring reactions that require co-option of distinct cosubstrates. Future efforts to integrate anthocyanin pathway genes into the genome of E. coli should also be undertaken to generate stable production strains lacking plasmids.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we found that coordinated, global perturbation of SAM biosynthesis was obtainable through a single CRISPRi intervention, leading to increased conversion through the anthocyanin O -methylation tailoring reaction. The metJ dysregulation strategy described in this and another recent report [25] should be useful for improving methylation of any natural product, but the general steps taken here should also be applicable for studying unique anthocyanin tailoring reactions that require co-option of distinct cosubstrates. Future efforts to integrate anthocyanin pathway genes into the genome of E. coli should also be undertaken to generate stable production strains lacking plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…Despite modest titers outlined here for the novel anthocyanin product P3G, very impressive and extensive work published during the preparation of this manuscript examined several solutions to SAM limitation in E. coli K-12 MG1655(DE3) lineages for production of vanillate, an O -methylated natural product that had been produced in E. coli previously but suffered from low titers [25]. Combined deregulation of SAM biosynthesis through metJ deletion, feedback desensitization of enzymes catalyzing committed or important biosynthetic steps, and deregulation of SAM regeneration improved de novo vanillate titers by twofold to approximately 400 mg/L [25]. These findings imply that SAM-dependent natural product biosyntheses in E. coli at industrially relevant titers will likely be achievable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein concentration was initially determined according to the Bradford method [11], with bovine serum albumin (BSA) as the protein standard. The SDS-PAGE consisted of 5 % stacking gel and 12 % separation gel.…”
Section: Protein Extraction and Sds-page Electrophoresismentioning
confidence: 99%